Numerical Analysis of Performance on Internal Flow for Contra-Rotating Small-sized Cooling Fan - Manshoor, Bukhari; Azman, Mohammad Shahril (Research Progress in Mechanical and Manufacturing Engineering, 2021)
A contra-rotating fan is basically two fans combine but rotate in a different direction. Many still do not familiar with the term “contra”, as the contra-fan itself is rarely used. Contra means different, which explain the two-fan blade rotating in opposite direction. The contra-rotating fan consists of the front blade that rotated in a clockwise direction and the rear blade rotated counterclockwise. A lot of energy conversion efforts has made in the past, in order to improve efficient airflow. From the previous study, it is shown that the contra-rotating fan had many advantages compared to the axial fan. counter-rotating axial-flow fans could be a promising way to achieve these requirements. This is because of the reduction of rotational speed and a better homogenization of the flow downstream of the rear rotor and produces very good aerodynamic performances. Computational Fluid Dynamic (CFD) software. The blades were designed using SolidWorks 2019 software and then been evaluate or simulate using Ansys 19.3. The contra-rotating fan setup was compared with another fan setup. The performance evaluations of contra-rotating are compared in terms of the airflow velocity parameters.